DISABILITY HIERARCHIES AND INTERNALISED ABLEISM IN FLANNERY O’CONNOR’S THE LIFE YOU SAVE MAY BE YOUR OWN - Malesela Montle; Heritage Moleke (Universitas Islam Sumatera Utara (UISU), 2026)
Flannery O’Connor’s The Life You Save May Be Your Own examines the ableist and exploitative attitudes affecting persons with disabilities. The text demonstrates how disability hierarchies intensify marginalisation based on the severity of impairments. It presents two characters with distinct disabilities: one physically impaired and the other psychologically impaired, whose experiences converge through shared marginalisation and exploitation. Through this convergence, O’Connor exposes not only ableism pointed at persons with disabilities by the able-bodied community, but also intra-community ableism, where individuals with lesser impairments marginalise those with more severe disabilities. Accordingly, this study employs a qualitative close reading approach to explore hierarchies within the disabled community and their impact on victimisation and marginalisation of persons with disabilities. The study finds that differing social valuations attached to disability contribute to the reproduction of internalized ableism. Less severely disabled characters exploit and marginalise those with greater impairments, perpetuating othering, systemic discrimination, and lived struggles within the disabled community. The analysis of these findings is grounded in Critical Disability Theory.